Can emotional stability buffer the effect of job stress on deviant behavior? - Ahmad, Aminah; Omar, Zoharah; Radzali, Farah Mardiana; Saidu, Mohammed Bashir (Science Publications, 2017)
The interrelationships between job stress, WDB and emotional stability have not been studied in a model to comprehend whether emotional stability could weaken the impact of job stress on employee deviant behavior. We tested a model on the moderating role of emotional stability, a personality factor, in the relationship between job stress and workplace deviant behavior. The model was developed based on the general strain theory and the integrated general model of workplace deviant behavior. Structural equation modeling analysis was conducted on survey data from 261 employees from six Malaysian public service agencies. Our results supported the proposed model. The stress-deviance relationship is significant. The stress-deviance linkage is stronger among employees who are less emotionally stable than those who are more emotionally stable. The results suggest that emotional stability as a personality factor plays a vital role in further understanding the impact of job stress on employee deviant behavior. Based on the results, the general strain theory and the integrated general model of workplace deviant behavior could serve as the bases for explaining the stress-deviance relationship and the moderating role of emotional stability.